A Study of Consumer Satisfaction Towards E-Banking Facilities Provided by Private Sector Banks with The Reference Vita City and Its Correlation with The Level of Education - Jadhav Sundar Dhairyasheel; Thorat Shubhada Sambhaji (Indonesian Journal of Educational Research and Technology, 2023)
Once upon a time, bank banking services do not provide multiple banking services. The customer of the bank is ca not use the e-banking services after some time banking sector analysis the market environment and provided the various types of banking services. Every customer is the king of the market. In the market, every businessman knows the demand of the customer and they produce the product which is satisfied their need and wants. Nowadays the banking sector adopts the new technology in their sector e-banking services plays an essential role in the banking sector. This facility attracts every customer to our bank If the banking services can not accept the new technology they do not survive very well in the market. E-banking services are provided to the customer with various types of facilities like Electronic fund transfer, mobile banking, Internet banking, Debit card, Credit card, and NEFT. All services are provided to the customer at less cost of transaction and it is very easy to use. This study helps to know the satisfaction of the customer towards E-banking facilities provided by private sector banks in Vita city.